Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Umkm Kerupuk Fajar Melalui Online Single Submission (OSS) - Furuhita, Fitri Aulia; Rizkiyah, Noor; Zuhri, Gideon Setyo Abuzar (Universitas Gajah Putih, Indonesia, 2023)
Micro, Small and Medium Enterprises or MSMEs are an important part of the economy of a region. MSME actors in Tlumpu Village, Sukorejo District, Blitar City are one of the urban villages that have a large number of MSMEs. There are various kinds of MSMEs in the Tlumpu Village, which vary widely in terms of products and services. One of the MSMEs in the Tlumpu Village is the Kerupuk Fajar MSME. MSME is a fairly large business and has been established since 2000. But UMKM Kerupuk Fajar does not yet have business legality. Therefore, Student Group 43 KKN-T MBKM UPN